Primitive sarcomas of the breast - Esteían, Alberto; Marella, Muzio; Gomez Fossati, Carlos; Vargas, Avelino Franco; Del Campo, Alberto; De Los Santos, Julio; Falconi, Luis (Cirugía del Uruguay, 1975)
Primitive sarcomas of the breast are a very heterogeneous group of tumors, only related to one another by their mesenchymal origin. Clinically, they are undistinguishable from other breast tumors, and in particular, from carcinomas. Definitive diagnosis can only be based on a complete histopathologic study. Simple breast roentgenology, cytologic punction and even partbiopsy may lead to errors. Each histopathologic type has a particular bio-pathology, which requires its own clinical and therapeutic approach. The surgical procedure then depends on the degree of extension and the type of tumor. Radical mastectomy is indicated in rhabdomyosarcoma, in undifferentiated liposarcoma and in hemagiosarcoma; in the rest, a simple mastectomy, or mastectomy associated with pectoral resection and/or axillary dissection is enough. The authors carry out a retrospective clinical and pathological analysis on 16 cases: 10 fibrosarcomas, 3 rhabdomyosarcomas, 2 hemangiosarcomas and 1 malignant mesenchymoma. The treatments applied were varied, in general choosing non-radical procedures. In 8 cases local recurrences occurred. Out of the 10 cases in which a long follow-up could be done, 8 have survived without signs of disease, from 2 to 16 years after surgery.